2019
DOI: 10.6035/languagev.2011.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Strategic construal of in and out in English particle verbs (PVs)

Abstract: 1The central aim of this work is to describe the strategic construal of in and out in English particle verbs. The term strategic construal assumes the following: 1) exploration of strategic thinking in L2 learning and processing, and 2) exploration of dynamic and subjective construction of meaning pertaining to the human ability to understand and portray the same situation in alternate ways (Langacker 1987). In other words, the paper relies on two theoretical paradigms with self-evident commonalities -a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…When L2 speakers are constructing meaning, they activate various cognitive processes that communicate with language, along with their knowledge of the world, and the knowledge of their L1. In our use of the concept of strategic construal and the theoretical framework it implies, we assume that L2 speakers are capable of constructing meaning and, therefore, paying attention to both form and meaning (Geld 2009a). Accordingly, if they are able to relate specific forms to specific meanings, they will also be able to make sense of idiomatic expressions and identify cognitive motivation behind their components.…”
Section: Strategic Construalmentioning
confidence: 99%
See 4 more Smart Citations
“…When L2 speakers are constructing meaning, they activate various cognitive processes that communicate with language, along with their knowledge of the world, and the knowledge of their L1. In our use of the concept of strategic construal and the theoretical framework it implies, we assume that L2 speakers are capable of constructing meaning and, therefore, paying attention to both form and meaning (Geld 2009a). Accordingly, if they are able to relate specific forms to specific meanings, they will also be able to make sense of idiomatic expressions and identify cognitive motivation behind their components.…”
Section: Strategic Construalmentioning
confidence: 99%
“…Naturally, what it is that particular speakers find salient in L2 depends on a number of language-internal and language-external factors. One of the languageexternal factors is their proficiency in L2 (Geld 2009a;Geld & Letica Krevelj 2011). Previous research on strategic construal has shown that more proficient speakers of English as L2 are more likely to observe a connection between form and meaning.…”
Section: Strategic Construalmentioning
confidence: 99%
See 3 more Smart Citations